1993
DOI: 10.1073/pnas.90.24.12000
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C is the inhibitory ligand that determines dominant resistance to lysis by NK1- and NK2-specific natural killer cells.

Abstract: Natural killer (NK) ceUs recognize alloantigens on normal cels. One of these alloantigens correlates with homozygosity for a dimorphism of HLA-C at positions 77-80, which is shared by a number ofHLA-C alleles. A second alleic alloantigen correlates with homozygosity for the alternative HLA-C dimorphism, which is shared by the remaning HLA-C alleles. Moreover, NK1-and NK2-specific NK ceUl lines can be generated by mixed leukocyte cultures in which donor and stimulator are homozygous for the alternative dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
303
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(306 citation statements)
references
References 53 publications
1
303
2
Order By: Relevance
“…Initial studies indicated a simple bipartite system in which KIR2DL2/3 recognizes HLA‐C allotypes with asparagine at residue 80 (the HLA‐C1 motif), and KIR2DL1 recognizes HLA‐C allotypes with lysine at residue 80 (the HLA‐C2 motif). Dimorphism at residue 44 of the KIR molecule causes these specificity differences, where KIR2DL2/3 has lysine and KIR2DL1 has methionine 36, 100, 104, 105. Crystal structures showed that K44 of KIR2DL2 forms a hydrogen bond with the N80 of HLA‐C1 99.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Initial studies indicated a simple bipartite system in which KIR2DL2/3 recognizes HLA‐C allotypes with asparagine at residue 80 (the HLA‐C1 motif), and KIR2DL1 recognizes HLA‐C allotypes with lysine at residue 80 (the HLA‐C2 motif). Dimorphism at residue 44 of the KIR molecule causes these specificity differences, where KIR2DL2/3 has lysine and KIR2DL1 has methionine 36, 100, 104, 105. Crystal structures showed that K44 of KIR2DL2 forms a hydrogen bond with the N80 of HLA‐C1 99.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…6 The HLA-C1 allotype, characterized by having asparagine at position 80, binds KIR 2DL2/3/2DS2. 7,8 The HLA-C2 allotype, characterized by lysine at position 80, is a ligand for 2DL1/S1. 7,8 Polymorphism within the HLA-B gene produces either Bw4 or Bw6 allotypes, the former of which are ligands for 3DL1 and possibly 3DS1.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The HLA-C2 allotype, characterized by lysine at position 80, is a ligand for 2DL1/S1. 7,8 Polymorphism within the HLA-B gene produces either Bw4 or Bw6 allotypes, the former of which are ligands for 3DL1 and possibly 3DS1. 9 Given the inherent complexity of both KIR and their HLA class I ligands and the fact that they segregate independently on different chromosomes, these cell surface molecules need to be considered together for functional interactions to be appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…KIR2DL2 and 2DL3 bind a subset of HLA-C allotypes containing an asparagine at amino-acid position 80 of the heavy chain (HLA-C1 alleles) and KIR2DL1 binds the remaining HLA-C allotypes with lysine 80 (HLA-C2 alleles). [19][20][21] KIR3DL1 binds 40% of the HLA-B allotypes containing a serologically defined Bw4 epitope 22,23 and KIR3DL2 binds HLA-A3/A11. 24,25 The strength of these interactions is highly sensitive to polymorphism of the KIR and HLA genes, as well as the HLA-bound peptide sequence.…”
Section: Introductionmentioning
confidence: 99%